Digital Human Modeling. Applications in Health, Safety, Ergonomics and Risk Management: Ergonomics and Health 6th International Conference, DHM 2015, Held as Part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings, Part II - Duffy, Vincent G.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The two-volume set LNCS 9184-9185 constitutes the constitutes the refereed proceedings of the 6th International Conference on Digital Human Modeling and Applications in Health, Safety, Ergonomics and Risk Management 2015, held as part of the 17th International Conference on Human-Computer Interaction, HCII 2015, held in Los Angeles, CA, USA, in August 2015. The total of 1462 papers and 246 posters presented at the HCII 2015 conferences was carefully reviewed and selected from 4843 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The total of 96 contributions included in the DHM proceedings were carefully reviewed and selected for inclusion in this two-volume set. The 52 papers included in this volume are organized in the following topical sections: anthropometry and ergonomics; motion modeling and tracking; human modeling in transport and aviation; human modeling in medicine and surgery; quality in healthcare.
Anthropometry and ergonomics -- Motion modeling and tracking -- Human modeling in transport and aviation -- Human modeling in medicine and surgery -- Quality in healthcare.
Keywords: Computer science; Health informatics; Information storage and retrieval; User interfaces (Computer systems).; Application software; Computers and civilization; Computer Science; User Interfaces and Human Computer Interaction; Health Informatics; Computers and Society; Information Systems Applications (incl. Internet).; Computer Applications; Information Storage and Retrieval; Electronic books